Jeremy Blake : Winchester. - Benezra, Neal; Blake, Jeremy; Schwarzer, Mitchell; Weil, Benjamin; Exhibition. Jeremy Blake : Winchester. SFMOMA (San Francisco Museum of Modern Art) San Francisco. 2005-02-19. 2005-08-14 (San Francisco : SFMOMA (San Francisco Museum of Modern Art) San Francisco, 2005)
In San Jose, California, stands an unlived-in mansion, a Victorian pile with 160 rooms, 40 staircases, 467 doors, and 10.000 windows. The house's eccentric chambers, tortuous hallways, and stairways to nowhere today stand as testament to the damaged, bereaved psyche of the lonely widow who designed it. Built on the tragic fortune of The Gun That Won The West, this is the Winchester Mystery House, the inspiration and setting for Jeremy Blake's new film trilogy. Melding Blake's signature digital abstractions with footage of the Winchester mansion, the work interrogates traditional cinematic modes of storytelling; cultural mythologies surrounding guns, violence, and the American West ; and the relationship between physical and simulated reality in the digital age. In this catalogue, the most authoritative publication on Blake's art to date, curator Benjamin Weil introduces the Winchester trilogy and discusses it in the context of the artist's career. Architecture critic Mitchell Schwarzer examines the San Jose mansion and its surroundings as a peculiar convergence of three built environments : the Winchester house, the aging Century Theatres complex across the street, and the Mediterranean-style Santana Row commercial development. Finally, lush plates presenting sequences from all three works are accompanied by artist statements that illuminate Blake's myriad motivations and rich symbolic vocabulary.
Engels
boek
Keywords: Blake, Jeremy